PRODUCTIVE SKILLS IN FOREIGN LANGUAGE TEACHING - Bahodirova, Nigora (Журнал иностранных языков и лингвистики, 2023)
Today, being able to communicate in a foreign language is becoming more and more prominent day by day. The importance of finding effective ways of teaching and learning them is increasing. There are a number of terms and concepts in foreign language teaching methodology. The term productive skills is widely used in foreign language teaching. This article aims to analyze productive skills and their characteristics in ELT teaching.